Impact of Deficit Irrigation on Maize Physical and Chemical Properties and Ethanol Yield. Issue 5 (2nd October 2013) - Liu, Liman; Klocke, Norman; Yan, Shuping; Rogers, Danny; Schlegel, Alan; Lamm, Freddie; Chang, Shing I.; Wang, Donghai
ABSTRACT: The objective of this research was to study the effect of irrigation levels (five levels from 102 to 457 mm of water) on the physical and chemical properties and ethanol fermentation performance of maize. Twenty maize samples with two crop rotation systems, grain sorghum–maize and maize–maize, were harvested in 2011 and evaluated at the Kansas State University Southwest Research‐Extension Center near Garden City, Kansas, under a semiarid climate. Results showed that maize kernel weight, density, and breakage susceptibility decreased as irrigation level decreased. Starch contents of maize samples grown under a low irrigation level were approximately 3.0% lower than those under a high irrigation level. Protein contents ranged from 9.24 to 11.30% and increased as irrigation level decreased. Maize flour thermal and rheological properties were analyzed by differential scanning calorimetry and the Micro Visco‐Amylo‐Graph‐U device. Starch gelatinization temperature increased significantly as irrigation level decreased, whereas starch pasting viscosity decreased as irrigation level decreased. Free amino nitrogen (FAN) was significantly affected by irrigation level: it increased as irrigation decreased. Ethanol fermentation efficiency ranged from 90.96 to 92.48% and was positively correlated with FAN during the first 32 h of fermentation ( r 2 = 0.645). Deficit irrigation had a negative impact on ethanol yield. The maize with lower irrigation yielded about 4.0% less ethanol (44.14 mL/100 g of maize) than maize with high irrigation (45.92 mL/100 g of maize). Residual starch contents in the distillers dried grains with solubles were in a range of 0.80–1.02%. In conclusion, deficit irrigation had a significant effect on physical properties, chemical composition, ethanol yield, and fermentation efficiency of maize.